The Fragility-Grievances-Conflict Triangle in the Middle East and North Africa (MENA) - Kivimaki, Timo; Jawad, Rana (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Several problems related to violence, grievances, and states' lack of legitimacy and capacity to manage economic, social, and political issues are clustered together as an interactive structure in the Middle East and Northern Africa (MENA) region. The effect of one of these problems is difficult to identify in the absence of analyses of the others. Global generalisations on the effects of these problems can bring us closer to the understanding of state fragility and the associated problems in the MENA region, although the study of MENA specifically also reveals region- and sub-region-specific features. Some of them pertain to the MENA region only, whereas others help develop the understanding and sophistication of global generalisations. This book offers a much-needed overview and several explanations on the otherwise confusing triangular problems of state fragility, grievance, and conflict, focusing on one of the conflict hotspots of the world. It compiles expertise on the triangular relationship between fragility, grievances, and conflict of an international MENA Social Policy Network. In addition to the analyses, two datasets are referenced, on which some of the book's chapters are based.